The Tanaka Line shaped the phylogeographic pattern of the cotton tree (Bombax ceiba) in southwest China. (June 2015) - Tian, Bin; Zhou, Zhili; Du, Fang K.; He, Chengzhong; Xin, Peiyao; Ma, Huancheng
Abstract: The Tanaka Line is considered to be an important phytogeographic boundary in southwest China, especially in Yunnan province. This Line has been deemed to separate East Asia's Sino-Himalayan and Sino-Japanese floras. However, it is not clear whether there is a special phylogeographic pattern for plants occurring across the Tanaka Line. To better understand the role of the Tanaka Line in shaping genetic structure of plant species occurring either side of this line, we employed Bombax ceiba, an economically and ecologically important tree species with a distribution across the Tanaka Line, as a proxy to study whether or not the Tanaka Line acts as a boundary to gene flow. We scanned and analyzed genetic variation at three chloroplast DNA fragments ( psb B- psb F, trn L- rpl 32 and psb I- psb K) within and among 17 natural populations (201 individuals). We identified eight chloroplast haplotypes (A-H) in total. Geographically, seven haplotypes were found southwest of the Tanaka Line, but only two haplotypes (B and H) were located northeast of the Tanaka Line. Meanwhile, both mismatch distribution analysis and environmental niche modeling (ENM) analysis suggested that multiple glacial refugia were maintained in the southwest range of B. ceiba during the last glacial maximum and that northeastern populations underwent strenuous retreatment during the Quaternary climatic oscillations. The present study highlights the importance of historical climate change and topographical circumstances in shaping population structure across the Tanaka Line.